Dino Cinel, The national integration of Italian return migration 1870-1929, Νέα Υόρκη 1991· Linda Reeder, Widows in white. Migration and the transformation of rural Italian women, Sicily, 1880-1920, Τορόντο 2003 - Τουργέλη Γιώτα (Μνήμων, 2012)
no abstract